Z. Ivinskis: the first objective researcher of St. Casimir's life - Jonas Boruta (Lietuvos Istorijos Studijos)
In the creative legacy of Z. Ivinskis we have a number of works dedicated to Casimir, Lithuania's saint of the 15th century. Apart from his monography "St. Casimir," published in New York in 1955, Z. Ivinskis had published four articles on this theme in the period 1953-58. How do these works of Z. Ivinskis differ from earlier writings dedicated to this theme? The first biography of St. Casimir was written by an Italian bishop, Zacharias Ferreri, already in the first decade of the 16th century. Later, authors—not excepting even the fairly critical and soberly-thinking famous bishop of Samogitia of the 19th century, Motiejus Valančius—merely repeated the poor information gathered by the first biographer. The Polish historian Fr. Papee evaluates the writings of Z. Ferreri and his followers as follows: "How nevertheless poor is the biography written by him! How a living historical personage in it is drowned in the fog of legendary asceticism!"